TRAINING ON TEMPLATE-BASED WRITING OF SCIENTIFIC ARTICLES FOR ENGLISH TEACHERS IN KEDIRI AND BANYUWANGI - Khusyairi, Johny A.; Riyanto, Edi; Afdholi, Nadya; Rosyida, Us; Cahyo, Pujo; Meyrasyawati, Dewi (Universitas Airlangga, 2024)
Writing scientific article becomes teachers obligation, because scientific publication is an important requirement for their promotion. In order to awaken and improve teachers' ability to write such publication, the Graduate Program of Literary and Cultural Studies (LCS) Universitas Airlangga conducted community service. This activity took form of training for writing scientific articles by using templates. This training was carried out in the form of delivering lectures and discussions. The team of trainers planned to expand the method in the form of workshop that is by writing practice and consultation at the next community service activity. The participants of this training were high school English teachers in Kediri and Banyuwangi. This activity was carried out separately in the two cities. By conducting this training, we found the enthusiasm of the teachers. The issues uttered for writing articles are also interesting and varied. Their hopes that the training can continue further and be carried out intensively shows that these teachers do need assistance in writing. Besides that, the training activities in these two cities indicates a snapshot of high school teachers in other areas who also need the same training and assistance.